Tools for Assessment of Country Preparedness for Public Health Emergencies: A Critical Review. (5th August 2021) - Haeberer, Mariana; Tsolova, Svetla; Riley, Paul; Cano-Portero, Rosa; Rexroth, Ute; Ciotti, Massimo; Fraser, Graham
ABSTRACT: Recent international communicable disease crises have highlighted the need for countries to assure their preparedness to respond effectively to public health emergencies. The objective of this study was to critically review existing tools to support a country's assessment of its health emergency preparedness. We developed a framework to analyze the expected effectiveness and utility of these tools. Through mixed search strategies, we identified 12 tools with relevance to public health emergencies. There was considerable consensus concerning the critical preparedness system elements to be assessed, although their relative emphasis and means of assessment and measurement varied considerably. Several tools identified appeared to have reporting requirements as their primary aim, rather than primary utility for system self-assessment of the countries and states using the tool. Few tools attempted to give an account of their underlying evidence base. Only some tools were available in a user-friendly electronic modality or included quantitative measures to support the monitoring of system preparedness over time. We conclude there is still a need for improvement in tools available for assessment of country preparedness for public health emergencies, and for applied research to increase identification of system measures that are valid indicators of system response capability.